Proliferation of neutral modes in fractional quantum Hall states - Inoue, Hiroyuki; Grivnin, Anna; Ronen, Yuval; Heiblum, Moty; Umansky, Vladimir; Mahalu, Diana (Nature communications, 2014)
The fractional quantum Hall effect is a canonical example of topological phases. While electric currents flow downstream in edge modes, neutral edge modes, observed only in hole-conjugate states and in ν =5/2, flow upstream. It is believed that the latter transport results from multiple counter-propagating channels—mixed by disorder that is accompanied by Coulomb interaction. Here we report on sensitive shot noise measurements that reveal unexpected presence of neutral modes in non-hole-conjugate fractional states; however, not in the integer states. Furthermore, the incompressible bulk is also found to allow energy transport. While density reconstructions along the edge may account for the energy carrying edge modes, the origin of the bulk energy modes is unidentified. The proliferation of neutral modes changes drastically the accepted transport picture of the fractional quantum Hall effects. Their apparent ubiquitous presence may explain the lack of interference of fractional quasiparticles—preventing observation of fractional statistics. The accepted picture of transport in the fractional quantum Hall effect regime is that neutral modes are present only in hole-conjugate fractional states. Inoue et al. show the presence of upstream neutral modes and energy transport through the bulk in all tested non-hole-conjugate fractional states.